Topical Photodynamic Therapy as a Treatment Option for Periocular Bowen's Disease: A Case Report - Reis,Joel (2021)
ABSTRACT Cutaneous squamous cell carcinoma in situ of the eyelid and periorbital skin malignancies is common and its management is demanding. Surgical excision is considered the first-line treatment, but these techniques have limitations. Topical photodynamic therapy is currently approved for the treatment of squamous cell carcinoma in situ in other areas, but the reports of its use in this sensitive anatomic location area are scarce. Herein we report the case of a 61-year-old-man with extensive periocular Bowen disease that was treated successfully with photodynamic therapy. Photodynamic therapy may be an option as neoadjuvant or curative therapy in selected cases, especially in sensitive anatomic locations where surgery might lead to distortion of the structures or where techniques as micrographically controlled surgery are not available.